2007
DOI: 10.1016/j.mcn.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel regional and developmental NMDA receptor expression patterns uncovered in NR2C subunit-β-galactosidase knock-in mice

Abstract: NMDA receptor "knock-in" mice were generated by inserting the nuclear β-galactosidase reporter at the NR2C subunit translation initiation site. Novel cell-types and dynamic patterns of NR2C expression were identified using these mice, which were unnoticed before because reagents that specifically recognize NR2C-containing receptors are non-existent. We identified a transition zone from NR2C-expressing neurons to astrocytes in an area connecting the retrosplenial cortex and hippocampus. We demonstrate that NR2C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 58 publications
7
87
1
Order By: Relevance
“…The generation of NR2A Ϫ/Ϫ (1) mice is reported in Sakimura et al (1995) and that of NR2C Ϫ/Ϫ (3) mice is in Lu et al (2006) and Karavanova et al (2007). Mouse pups were killed by decapitation in agreement with the guidelines of the AVMA Panel on Euthanasia and the Georgetown University Animal Care and Use Committee.…”
Section: E T H O D Smentioning
confidence: 99%
“…The generation of NR2A Ϫ/Ϫ (1) mice is reported in Sakimura et al (1995) and that of NR2C Ϫ/Ϫ (3) mice is in Lu et al (2006) and Karavanova et al (2007). Mouse pups were killed by decapitation in agreement with the guidelines of the AVMA Panel on Euthanasia and the Georgetown University Animal Care and Use Committee.…”
Section: E T H O D Smentioning
confidence: 99%
“…Thus, the onset of erbb2/erbb4 inactivation (P6) (Fig. 1 B) may appear too close to the induction of NR2C expression (P6) (Karavanova et al, 2007) to fully exclude a role of NRG/ErbB-dependent signaling in this process in the erbb2/erbb4 dKO mice. It should be noted, however, that both the degree of recombination and the normal development of NR2C mRNA levels in erbb2/erbb4-deficient mice are averaged over the entire cerebellum.…”
Section: Discussionmentioning
confidence: 98%
“…One example in the CNS is the developmental switch in neurotransmitter receptor expression in postmigratory cerebellar granule neurons that is thought to be induced by the mossy fibers innervating them. These cells express the NR2B receptor subunit at late embryonic and early postnatal stages, but switch to the NR2C subunit beginning in the second postnatal week and extending to the end of the first month (Monyer et al 1994, Karavanova et al 2007. Assaying individual granule neurons by single-cell PCR showed that NR2C was expressed specifically in postmigratory granule cells starting at the end of the first postnatal week and continuing until the end of the first postnatal month when all granule cells have completed migration (Durand et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations